Haunted house film studies: the mother character as the victim of hauntings in Malaysian and Hollywood haunted house films - Ahmad Muhyiddin Yusof; Nur Azmina Mohamad Zamani; Naizrul Mubin Mohd Noor; Muhammad Aiman Abdul Halim (Penerbit Universiti Kebangsaan Malaysia, 2021)
It is apparent that there is a steady development and progress of haunted house films both in Malaysia and Hollywood in many of its important moviemaking elements which are inspired by Gothic. Furthermore, other crucial elements which have been adapted by local and Hollywood filmmakers in directing the haunted house movies are such as inspired from real events’, novels, local ghosts, gender, urban legends, and folk tales. However, have we ever noticed about the role of female characters in most of these haunted house films where these female characters play important roles as being the ones who are usually possessed in these movies? Hence, the main objective of this paper is to dissect, explore and differentiate the haunted house filmic patterns both in Malaysia and Hollywood by looking in detail on how the mother characters are used as the characters or victims of hauntings in these haunted house movies. To achieve this, a corpus of data that encompasses two haunted house films from Malaysia and Hollywood namely Congkak, and The Conjuring were used a part of comparative literature. To identify the convergence and divergence aspects in the corpus mentioned above in further detailing on the notion of the female character as the victim of hauntings, the study has utilised two important concepts as its’ methodological approach namely Vladimir Propp’s concept of structuralism and Comparative Literature disciplines. Analysis conducted uncovers that the roles of mother characters in these films through the filmic patterns and events which occurred to these mother characters can be linked to directors’ ideology that they are trying to deliver through their films where women are frail, weak, and always need saving by others. The study has successfully detailed out how this will lead to a social construct and ideology where women are physiologically and physically weak, men are strong.